ผลของแบคทีเรียปนเปื้อนต่อการเจริญและการผลิตเอทานเอลของ Saccharomyces cerevisiae - เกศกมล ไทยทอง (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
Bacterial contamination in industrial ethanol fermentation by Saccharomyces cerevisiae was due to the use of non-sterile molasses as a raw material and also the contamination during fermentation process. The present work reported on isolation of major contaminated bacteria in molasses and also in fermentation broth and using bacterial growth characters inside and on the surface of solid medium as a preliminary classification. It was found that the major contaminated bacteria in molasses was spore-forming bacteria belonging to genus Bacillus. However, it had poor growth in molasses medium, therefore, it had less effect on ethanol fermentation. The contaminated bacteria in fermentation broth was non-spore-forming bacteria with no catalase and oxidase activity. It was classified to be in genus Lactobacillus and designated as Bacteria J. It had good growth in molasses medium. Ethanol fermentation in the presence of varied initial molasses concentrations of 60, 120, 180 and 220 g/l showed that Bacteria J reducedethanol production when molasses at 60 and 120 g/l were used. This was due to the competition between the yeast and Bacteria J for sugar utilization. However, at higher concentration of 180 and 220 g/l, Bacteria J had no effect on ethanol production and on specific ethanol production rate although the specific growth rates of both yeast and the bacteria were reduced